17m-11m-4m=12

Simple and best practice solution for 17m-11m-4m=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17m-11m-4m=12 equation:



17m-11m-4m=12
We move all terms to the left:
17m-11m-4m-(12)=0
We add all the numbers together, and all the variables
2m-12=0
We move all terms containing m to the left, all other terms to the right
2m=12
m=12/2
m=6

See similar equations:

| 8s-5s+s+3s=14 | | x/11(13)=-6 | | 8x2+7x+2=0 | | 4y•18=42 | | -p-4p+9p=-16 | | 3x+5=9x=6 | | x/2-16=-21 | | 23=-q | | 3(x+5)+8=2x+50 | | 5(a)+6=17 | | 2r+r-r=14 | | 2x+6+5x=5+3x+29 | | 5x+25=30x+125 | | (1/5+7s)(1/19-8s)=0 | | 17z+5z-19z+3z=18 | | Y=15x+100 | | (4+z)(5z+6)=0 | | 2r+4R-3r=12 | | 4(5x+2)=-2(x+5)+3 | | -7(x-8)+6=62 | | 2x^+4×+4=336 | | R+4R-4r=15 | | 2g-g-g+3g=6 | | 5y+13=-8y-8 | | 3(-4x+4)=156 | | 2x^+4×+4=340 | | y+1.75=9.33 | | 14-3y=13 | | 9d-8d=6 | | 5=9+4c | | w-5.7=8.51 | | x+27=7 |

Equations solver categories